2021
DOI: 10.11152/mu-3068
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Multiparametric Ultrasound and Fine Needle Aspiration Cytology evaluation of parotid gland tumors: which is the best technique?

Abstract: Aims: To evaluate the pre-surgical diagnostic value of Multiparametric Ultrasound (MPUS) and Fine Needle Aspiration Cytology (FNAC) in differentiating parotid gland tumors, comparing the results with histology. Materials and methods:The study enrolled 84 patients with parotid gland lesions surgically treated in a single tertiary center and evaluated by MPUS. Each patient underwent FNAC. Histological examination was considered the gold standard. Results: Histology identified 62 benign tumors and 22 malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…MRI can also be combined with fine-needle aspiration cytology (FNAC) to enhance diagnosis. Imaging techniques are easily and safely applied to lesions ( 23 , 24 ). Ultrasound-guided puncture biopsy is safe and effective for adrenal lacrimal lesions, including identifying benign and malignant causes and reducing or avoiding invasive surgical biopsies in most patients ( 25 ).…”
Section: Invasive Examinationmentioning
confidence: 99%
“…MRI can also be combined with fine-needle aspiration cytology (FNAC) to enhance diagnosis. Imaging techniques are easily and safely applied to lesions ( 23 , 24 ). Ultrasound-guided puncture biopsy is safe and effective for adrenal lacrimal lesions, including identifying benign and malignant causes and reducing or avoiding invasive surgical biopsies in most patients ( 25 ).…”
Section: Invasive Examinationmentioning
confidence: 99%
“…It appears to be a promising diagnostic tool, especially in combination with clinical complaint assessment [ 4 , 5 ]. Guiban et al in 2021 suggested that “the combination of B-mode US and CEUS greatly improved the sensitivity of the CEUS performed individually and presented remarkable accuracy, with the potential to reduce the number of invasive procedures” [ 6 ]. Saito et al in 2020 reported that “CEUS is a simple, safe, and noninvasive examination for patients that can be performed conveniently in real-time and could help differentiate PMA from WT in salivary glands” [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al in 2020 reported that “CEUS is a simple, safe, and noninvasive examination for patients that can be performed conveniently in real-time and could help differentiate PMA from WT in salivary glands” [ 7 ]. Papers present in the literature suggest that there is a constant need for further studies with large patient groups [ 4 , 5 , 6 , 7 ]. The authors had access to a relatively large group of patients who underwent preoperative contrast-enhanced ultrasound (CEUS) examination.…”
Section: Introductionmentioning
confidence: 99%